2021
DOI: 10.3390/ijms222011261
|View full text |Cite
|
Sign up to set email alerts
|

Placental Ischemia Says “NO” to Proper NOS-Mediated Control of Vascular Tone and Blood Pressure in Preeclampsia

Abstract: In this review, we first provide a brief overview of the nitric oxide synthase (NOS) isoforms and biochemistry. This is followed by describing what is known about NOS-mediated blood pressure control during normal pregnancy. Circulating nitric oxide (NO) bioavailability has been assessed by measuring its metabolites, nitrite (NO2) and/or nitrate (NO3), and shown to rise throughout normal pregnancy in humans and rats and decline postpartum. In contrast, placental malperfusion/ischemia leads to systemic reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 234 publications
1
7
0
Order By: Relevance
“…It has also been suggested to treat PE by modulating the NOS coupling [9,12,13]. Indeed, NOS coupled to its cofactors produces NO, whereas uncoupled NOS produce NO as well as the superoxide anion (O 2 − ), a ROS.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested to treat PE by modulating the NOS coupling [9,12,13]. Indeed, NOS coupled to its cofactors produces NO, whereas uncoupled NOS produce NO as well as the superoxide anion (O 2 − ), a ROS.…”
Section: Introductionmentioning
confidence: 99%
“…The placental Atlas Tool was also developed to create a shared platform for placental data research 36 . Additionally, previous studies have demonstrated a strong association between the onset and progression of preeclampsia and placental dysfunction during early pregnancy [37][38][39] . The placenta in pregnancies affected by preeclampsia undergoes a constantly changing and unhealthy metabolic state throughout gestation 40 .…”
Section: Discussionmentioning
confidence: 92%
“…Treatment of caveolae with oxidized LDL also ablates NOS3 activity, which can be restored by cholesterol treatment [137] [138] [139]. Studies of mice with absent NOS3 function show an exaggerated response to VEGF blocking factors with increased hypertension, hepatic dysfunction, thrombocytopenia, and renal dysfunction [140], all symptoms of human preeclampsia.…”
Section: Endothelial Nitric Oxide Synthase Signalingmentioning
confidence: 99%